Research and recovery: Can patient participation in research promote recovery for people with complex post‐traumatic stress disorder, CPTSD? - Catherine Matheson; Elizabeth Weightman (Wiley, 2021)
Abstract Background A new diagnosis of complex post‐traumatic stress disorder, CPTSD, has been agreed by the World Health Organization, WHO, and evidence is needed for what psychological treatment might be effective, particularly from those with experience of the disorder. We used a novel participatory approach to explore patient views and simultaneously studied the impact on the patient researchers of the research process itself. In this paper, we report on the latter section of the study how the involvement in research of patients with CPTSD affected their mental health. Symptoms of CPTSD may include emotional dysregulation, feelings of self‐worthlessness and difficulties in relationships. Objective The aim of this study section was to explore whether patients' mental health could be promoted through empowering them to participate in research on CPTSD. Design The study had a qualitative, participatory design. The clinician who led the research (first author) held group meetings with patient researchers to explore the impact of the research process. The clinician also kept notes on the process in a reflective log. Setting and participants Six patient researchers participated in research with other patients with lived experience of CPTSD in an NHS outpatient unit in a London hospital. Intervention studied The research process itself was analysed in group meetings with researchers which the clinician recorded and transcribed. Findings Participation in research may promote increased self‐confidence and social inclusion for those with CPTSD. Conclusion Involvement in research may be seen as an empowering intervention because patients felt it contributed to recovery.